Procedure for Distributing Remaining Business Proceeds Based on Membership in the XYZ Cooperative - Lisa Harnanda; Susilowati, Endah (Equity: Jurnal Akuntansi, 2025)
Cooperatives are business entities that are built on the principle of family with the aim of improving the welfare of their members. cooperative that meets the economic, social, and welfare needs of its members. One of them is the XYZ Cooperative. Cooperatives are formed to support the economic welfare of their members. This study aims to understand how the process of distributing the remaining business results (SHU) is distributed to cooperative members. This research was conducted with a descriptive qualitative approach, where data was collected through the process of observation, interviews, and document collection for approximately one year. The Business Surplus (SHU) is not only a form of appreciation for the active participation of members in cooperative activities, but also functions as an incentive to increase member involvement in the future. The distribution of the Business Surplus (SHU) is carried out fairly and transparently in its technicalities so that it can build member trust in the management of the cooperative. Thus, the Business Surplus (SHU) plays a role as one of the main factors in encouraging the sustainability of cooperatives and increasing the economic welfare of members.